Mitigating fines migration in low salinity water flooding of clay rich sandstones using TiO2 Saponin Zr nanocomposites - Yuman Li; Farag M. A. Altalbawy; Nikunj Rachchh; T. Ramachandran; Aman Shankhyan; A. Karthikeyan; Dhirendra Nath Thatoi; Deepak Gupta; Mohammad R. K. M. Al-Badkubi; Dilsora Abduvalieva; Samim Sherzod; Mohammad Mahtab Alam (Scientific Reports)
Abstract Mitigating formation damage due to fines migration is crucial for maintaining reservoir productivity in enhanced oil recovery (EOR) processes. This research introduces a novel composite, Titanium dioxide nanoparticles coated with Saponin and Zirconium (TiO2@Saponin/Zr(IV)), synthesized via a sol–gel method, to address this challenge, particularly in low salinity water injection scenarios. Characterization through FT-IR confirmed successful functionalization, indicated by the Zr–O band at 480 cm−1 and saponin bands around 1030–1085 cm−1 and 2919–2850 cm−1. Zeta potential measurements showed that in low salinity brine, quartz and kaolinite exhibited highly negative potentials of − 32 mV and − 45 mV, respectively, while TiO2@Saponin/Zr(IV) displayed a positive potential of + 19 mV. Importantly, mixtures of quartz and kaolinite with TiO2@Saponin/Zr(IV) in low salinity conditions resulted in moderated zeta potentials of + 3 mV and − 2 mV, indicating surface charge modulation. Core flooding experiments further validated the composite’s effectiveness. Injecting high salinity water resulted in a minor permeability reduction from 90 to 78 mD, while low salinity water injection caused a drastic drop from 90 to 8 mD. However, with the introduction of 0.5 wt% TiO2@Saponin/Zr(IV) in low salinity water, the permeability reduction was significantly controlled, decreasing from 90 to 85 mD. These quantitative results demonstrate that TiO2@Saponin/Zr(IV) effectively mitigates fines migration by modifying surface charge and preserving permeability, offering a promising solution for formation damage control and enhanced oil recovery.